2017
DOI: 10.1159/000454862
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Testosterone during the Minipuberty of Infancy

Abstract: Background: The hypothalamic-pituitary-gonadal axis is transiently activated during the postnatal months in boys, a phenomenon termed “minipuberty” of infancy, when serum testosterone (T) increases to pubertal levels. Despite high circulating T there are no signs of virilization. We hypothesize that free T as measured in saliva is low, which would explain the absence of virilization. Methods: We measured serum total T and free T in saliva using liquid chromatography-tandem mass spectrometry (LC-MS/MS) in 30 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
1
4
1
Order By: Relevance
“…On the other hand, and similar to some previous studies [12,13,15], in boys, serum testosterone concentrations were correlated with LH, and both hormones showed attenuation of after 3 months of age in mini-puberty. However, higher size of penis and penile circumference observed in older male infants during mini-puberty which was unrelated to measured total testosterone concentrations.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, and similar to some previous studies [12,13,15], in boys, serum testosterone concentrations were correlated with LH, and both hormones showed attenuation of after 3 months of age in mini-puberty. However, higher size of penis and penile circumference observed in older male infants during mini-puberty which was unrelated to measured total testosterone concentrations.…”
Section: Discussionsupporting
confidence: 90%
“…This study’s results supported our hypothesis that testosterone would a better predictive hormonal biomarker for physical growth and socioemotional development among VLBW infants than cortisol. Elevated testosterone levels, which were higher than those in other studies (Contreras et al, 2017; Fang et al, 2017), were longitudinally associated with physical growth delays over the 2 years of life. Such findings might have occurred because elevated testosterone levels were found to be related to preterm and low birthweight births in both human and animal studies (Cho et al, 2012; Quinn et al, 2014).…”
Section: Discussioncontrasting
confidence: 63%
“…First, two studies examined the associations between T and child health including autistic spectrum disorder (El-Baz et al, 2014;Kung et al, 2016), whereas nine studies examined the associations of T levels with child development including physical growth (bodyweight, length, body mass index, skinfold triceps) (Becker et al, 2015;Kiviranta et al, 2016), motor and language development (Cho et al, 2017;Whitehouse et al, 2012), pubertal transition (Mouritsen et al, 2014), anogenital distance in neonates (Avidime et al, 2011;Jain et al, 2018;Kareem et al, 2020), and postnatal activation of HPG axis after insulin injection (de Jong et al, 2012). The second category included the five studies that aimed to identify T measurements with greater accuracy and precision by comparing methods and materials (Ankarberg-Lindgren & Norjavaara, 2015;Contreras et al, 2017;Fang et al, 2017;Hamer et al, 2018;Knickmeyer et al, 2011). In the third category, four studies developed a method that was capable of the simultaneous measurement of multiple hormones (Kushnir et al, 2010;Olisov et al, 2019;Salameh et al, 2010;Shen et al, 2009).…”
Section: Problem Statements and Aims Of Selected Studiesmentioning
confidence: 99%
“…Those studies compared methods including second-generation immunoassays and LC/MS (Hamer et al, 2018), RIA and LC/MS (Ankarberg-Lindgren & Norjavaara, 2015), EIA and 2D:4D ratio (Knickmeyer et al, 2011), and LC/MS and RIC (Fang et al, 2017). Those studies also compared saliva and serum (Contreras et al, 2017) and urine, saliva, and serum (Fang et al, 2017). Hamer et al ( 2018) measured total T levels with two widely used second-generation immunoassays (the Architect and the Elecsys second-generation T assays) and LC/MS concurrently and reported that second-generation immunoassays overestimated T levels in neonates.…”
Section: Et Almentioning
confidence: 99%
See 1 more Smart Citation